EXPRESSIVE SPEECH ACTS IN YOUTUBE COMMENTS: A PRAGMATIC ANALYSIS OF PRINCE EA'S VIDEOS - Irawansyah, Irawansyah; Kurniawan, Iwan; Caresta, Vionica Sandra (University of Kuningan, 2024)
The growing volume of comments from online users expressing their opinions about Prince EA's video's content—which brought up issues with the educational system was the driving force for this study. The expressions used by netizens in the comments section have a certain meaning, and it's critical to grasp this meaning to avoid miscommunication and guarantee clear communication. Pragmatics' expressive speech act theory sheds light on this occurrence. The purposes of this study were to identify the various forms of expressive speech actions that may be found in Prince EA's YouTube channel's comment section and to explain the significance of these acts. The comments from Prince EA's videos were used in this study's descriptive qualitative analysis,